Country-Specific Determinants of Intra-Industry Trade in India. Issue 3 (August 2019) - Bagchi, Sagnik; Bhattacharyya, Surajit
A distinctive feature of India's trade liberalization has been a significant rise in the magnitude of intra -industry trade (IIT). India's total IIT is substantially large with high and upper-middle -income group countries and dominated by low vertical IIT. Particularly during the second phase of economic reforms, magnitude of India's vertical IIT with high-income group of countries had increased ; while there had been a marginal decline in horizontal IIT. This article identifies some of the determinants of India's total IIT as well as vertical and horizontal IIT with her major trading partners from 1990 to 2014. The convergence in the level of economic development between India and her trading partner(s) positively influences total IIT and its two broad forms. Similarity in relative factor endowments and regional trade agreement through South Asian Free Trade Area (SAFTA) is found to promote horizontal IIT. Having a large market size, the distortionary impact of tariff has not been able to dampen the magnitude of India's IIT. Relative depreciation of trading partner's real exchange rate enhances India's imports and inhibits the growth of total and vertical IIT. Geographical distance adversely affects all forms of IIT. JEL Codes: C23, F14